1998
DOI: 10.1021/jf980724i
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Competitive Adsorption on Flocculation and Rheology of High-Pressure-Treated Milk Protein-Stabilized Emulsions

Abstract: The effect of high-pressure treatment (HPT) on the droplet-size distribution and small-deformation rheology of oil-in-water emulsions containing beta-lactoglobulin and a nonionic surfactant or sodium caseinate has been investigated at neutral pH. Addition of Tween 20 (polyoxyethylenesorbitan monolaurate) to a beta-lactoglobulin-stabilized emulsion results in competitive displacement of the adsorbed globular protein film and, following HPT, the formation of a less flocculated emulsion. The age of the beta-lacto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Liquidlike emulsions can be converted into solid-like emulsion gels on heating [111]. Static high-pressure treatment of ␤-lactoglobulin in emulsions can also have a significant influence on protein aggregation and emulsion stability [112][113][114].…”
Section: 4ˇ-lactoglobulinmentioning
confidence: 99%
“…Liquidlike emulsions can be converted into solid-like emulsion gels on heating [111]. Static high-pressure treatment of ␤-lactoglobulin in emulsions can also have a significant influence on protein aggregation and emulsion stability [112][113][114].…”
Section: 4ˇ-lactoglobulinmentioning
confidence: 99%
“…A considerable amount of research has been performed on the stability of WPI and β-lactoglobulin emulsions under high pressure (Dickinson & James, 1998;Dickinson & James, 1999;Galazka, Dickinson, & Ledward, 1996;Galazka, Ledward, Dickinson, & Langley, 1995). It has been shown that HP treatment of emulsions under relatively severe pasteurisation conditions (800 MPa, 30 min) is less destabilising for an emulsion made with β-lactoglobulin than a mild heat treatment (Dickinson & James, 1999) and has little effect on the stability of a whey protein stabilised emulsion (Galazka et al, 1995). High-pressure sterilisation is a relatively novel development in this field where pressure and heat together result in sterilisation of food products.…”
Section: Introductionmentioning
confidence: 99%
“…Surfactant-protein interactions have been studied using conductivity [5,6], chromatography [5], axisymmetric drop shape analysis [7], FTIR [8][9][10], circular dichroism [11,12], fluorescence [13,14], and direct calorimetry [15][16][17][18]. It has been proposed that surfactants may interact with proteins directly by competing for oil-water or air-water interfaces [19,20] and by binding to them thereby leading to substantial changes in the protein conformation [21,22]. Alterations in the molecular characteristics of globular proteins due to their interactions with surfactants may lead to changes in their ability to bind other molecules; i.e.…”
Section: Introductionmentioning
confidence: 99%